2009
DOI: 10.1007/s11695-009-9965-9
|View full text |Cite
|
Sign up to set email alerts
|

A Surgical Rat Model of Sleeve Gastrectomy with Staple Technique: Long-Term Weight Loss Results

Abstract: We have created a surgical rat model of experimental SG model, enabling the further study of biochemical and hormonal parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
(22 reference statements)
4
20
1
3
Order By: Relevance
“…The transient reduction in food intake and weight gain observed in our study is consistent with other studies in obese and non-obese rodents where SG surgery was shown to decrease body weight as well as cumulative food intake for up to 2-6 wks. (35,37,80,122). In the current study, IT surgery decreased food intake for 4 weeks and weight gain for 3 weeks.…”
Section: Markers Of Glucose Metabolism In Adipose Tissuesupporting
confidence: 46%
See 1 more Smart Citation
“…The transient reduction in food intake and weight gain observed in our study is consistent with other studies in obese and non-obese rodents where SG surgery was shown to decrease body weight as well as cumulative food intake for up to 2-6 wks. (35,37,80,122). In the current study, IT surgery decreased food intake for 4 weeks and weight gain for 3 weeks.…”
Section: Markers Of Glucose Metabolism In Adipose Tissuesupporting
confidence: 46%
“…In order to minimize chances of leakage, the staple line was reinforced with 6/0 silk (Ethicon, Ontario, Canada) continuous suture on staple line (122). The abdominal wall was closed with running 4/0 silk suture, and the skin was sewed with a 3/0 silk suture.…”
Section: Sleeve Gastrectomymentioning
confidence: 99%
“…However, this period is equivalent to 3 human years [19]. Although we could not exclude the potential for weight regain after SG, other investigators have demonstrated that weight loss is maintained at 15 weeks after SG in rodents [20,21]. In human beings, the failure of weight lost after SG has been explained by the dilatation of the stomach.…”
Section: Discussionmentioning
confidence: 88%
“…However, this time period is the equivalent of 6 human years [28,29]. While we cannot exclude the potential for weight regain following sleeve gastrectomy, other investigators have demonstrated that weight loss is maintained at a 15-week time point following sleeve gastrectomy in rodents [30,31]. Although we still consider our results as preliminary, they warrant a larger comprehensive study, one which would include more rats in order to evaluate more precisely the role of antioxidant genes in obesity pathogenesis.…”
Section: Discussionmentioning
confidence: 81%